2008
DOI: 10.1080/14992020802307370
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive development in children with cochlear implants: Relations to reading and communication

Abstract: The purpose of the present article is to present an overview of a set of studies conducted in our own laboratory on cognitive and communicative development in children with cochlear implants (CI). The results demonstrate that children with CIs perform at significantly lower levels on the majority of the cognitive tasks. The exceptions to this trend are tasks with relatively lower demands on phonological processing. A fairly high proportion of the children can reach a level of reading comprehension that matches… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
64
1
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(77 citation statements)
references
References 24 publications
8
64
1
4
Order By: Relevance
“…Consistent with previous studies [10,25], similar performance levels were evident for complex as well as for visual working memory in NH and the whole group of DHH children. This was not apparent for DHH with weak initial PhPS.…”
Section: Working Memory Capacity and Other Measures Pre Interventionsupporting
confidence: 79%
See 2 more Smart Citations
“…Consistent with previous studies [10,25], similar performance levels were evident for complex as well as for visual working memory in NH and the whole group of DHH children. This was not apparent for DHH with weak initial PhPS.…”
Section: Working Memory Capacity and Other Measures Pre Interventionsupporting
confidence: 79%
“…The less efficient lexical access of DHH may have several reasons. First, it may reflect a less developed semantic network related to a reduced auditory stimulation during critical developmental periods in the DHH child's life [7,8,[10][11][12]. This probably leaves the DHH child with a poorer lexical network (fewer lexical representations and weaker links between them) in long-term memory.…”
Section: Working Memory Capacity and Other Measures Pre Interventionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Moog's report [2002] of a small group that included only 17 individuals showed that more than 70% scored within the average range for reading of NH children at their age. The recent literature has shown that children with CIs can reach levels of reading comprehension comparable to those of NH children, although not all of them do so [Geers et al, 2008;Lyxell et al, 2008]. Archbold et al [2008] conducted a follow-up study that included 105 children and found an overall mean reading delay of 2.2 years after 7 years of device use.…”
Section: Introductionmentioning
confidence: 99%
“…Archbold et al [2008] conducted a follow-up study that included 105 children and found an overall mean reading delay of 2.2 years after 7 years of device use. In their study of cognitive and communicative development, Lyxell et al [2008] found that a fairly high proportion of the hearingimpaired children with CIs can reach a level of reading comprehension that matches NH children, despite the fact that they have relatively poor phonological skills. Johnson and Goswami [2005] examined the phonological awareness skills of children with CIs and compared the reading ability among groups of deaf children who used CIs, hearing aids and age-matched hearing children.…”
Section: Introductionmentioning
confidence: 99%